Optimization of Ultrasound-Assisted Extraction of Phenolic Compounds from Black Locust (Robiniae Pseudoacaciae) Flowers and Comparison with Conventional Methods - Ivana Savic Gajic; Ivan Savic; Ivana Boskov; Stanko Žerajić; Ivana Markovic; Dragoljub Gajic (MDPI AG, 2019)
The aim of this study was to optimize the ultrasound-assisted extraction of phenolic compounds from black locust (Robiniae pseudoacaciae) flowers using central composite design. The ethanol concentration (33−67%), extraction temperature (33−67 °C), and extraction time (17−33 min) were analyzed as the factors that impact the total phenolic content. The liquid-to-solid ratio of 10 cm3 g−1 was the same during extractions. The optimal conditions were found to be 59 °C, 60% (v/v) ethanol, and extraction time of 30 min. The total phenolic content (TPC = 3.12 gGAE 100 g−1 dry plant material) and antioxidant activity (IC50 = 120.5 µg cm−3) of the extract obtained by ultrasound-assisted extraction were compared with those obtained by maceration (TPC = 2.54 gGAE 100 g−1 dry plant material, IC50 = 150.6 µg cm−3) and Soxhlet extraction (TPC = 3.22 gGAE 100 g−1 dry plant material, IC50 = 204.2 µg cm−3). The ultrasound-assisted extraction gave higher total phenolic content and better antioxidant activity for shorter extraction time so that it represents the technique of choice for the extraction of phenolic compounds. The obtained extract, as the source of antioxidants, can be applied in the pharmaceutical and food industries.